Strong identities and endorsement of human rights: Conflictive or complementary? - Ziemes, J.; Abs, H. (South African Journal of Higher Education, 2017)
In higher education, students are exposed to people with diverse backgrounds and opinions and frequently are challenged to participate in scientific discussions on controversial issues. The article discusses the implications of two theoretical approaches within psychology for the meaning of identity in dealing with diversity. Social and developmental psychologists have opposing views on identity: While the former claim that a strong sense of identity leads to competition for resources, to intolerance, to the devaluation of outgroups and, finally, to conflict, the latter argue that a weak sense of identity leads to totalitarian ideologies and intolerance towards deviating beliefs. We review literature on the implications and effects deriving from social and developmental psychology and integrate them in a model which explains how building a strong sense of identity can promote tolerance and the endorsement of human rights. In particular, we explore the importance of tolerance defined as acting towards one another in a spirit of brotherhood because the devaluation of the ‘other’ often is seen as the first step towards violence.